Neighborhood change in Cincinnati, Ohio, 2000-2016: The effect of the Great Recession. (2nd January 2023) - Ravuri, Evelyn
ABSTRACT: The Great Recession of 2008 had a tremendous impact on the economic vitality of neighborhoods in the cities of the U.S. This paper looks at the effect that the Recession had on neighborhood change in Cincinnati (Hamilton County). The county's 222 census tracts are classified into five categories: poor; urban-upgrading; working-class; middle-class, and elite tracts. 31.1% of census tracts changed their classification between 2000 and 2016 and most of this changed resulted in a downgrading of the tract's status from 2000. Tracts which economically upgraded were in areas of the city which received large financial investments after 2000 for urban revitalization. Several working-class/upper middle-class tracts at the suburb-city interface downgraded between 2000 and 2016. It is likely that many of these tracts were adversely affected by the housing crisis and Great Recession which significantly affected the welfare of working-class/middle-class households.